Proyecto de factibilidad para la creación de una microempresa productora de llaveros de resina con motivos culturales y su comercialización a los turistas de la Basílica del Cisne de la provincia de Loja - Macas Agüinzaca, Sonia María (2015)
The present thesis work, is titled "Project of feasibility for the creation of a microenterprise producer of key rings of resin with cultural reasons and its commercialization to the tourists of the basilica of El Cisne of the province of Loja." As objectives they thought about: To determine the feasibility for the creation of a microenterpriseproducer of key rings of resin with cultural reasons and their commercialization to the tourists of the Basilica of El Cisneof the provinceof Loja." To make a market study to establish the offer and the demand of the product, to elaborate the respective technical study that helps to institute such factors as: size and localization of the microenterprise, technological component and organizational structure. To design the organizational managerial structure, in which it will consist: the legal base of the constitution of the microenterprise, the hierarchical levels of authority, flowcharts and the different types of manuals. To develop an economic study that facilitates to detail the investment requirements, as well as the sources that are required for the financing of this project; to carry out the Financial pertinent Evaluation of the project, for I will appeal it to the approaches of financial evaluation as they are: Current Net (Van) Value, Appraises It Interns of Return (TIR), Relationship Benefits Cost (RB / C), Period of Capital Recovery and the Analysis of Sensibility. To base the present thesis, the literary revision was made in the same one it is given to know the with respect to the production of key rings of resin. During the investigation some such methods were used as the scientific, analytic-synthetic, inductive-deductive method; it was also appealed to the direct observation which facilitated to determine the existent problem; as well as the survey that after being had established the size of the sample, they were applied 400 tourists that visit the Basilica of El Cisne of the province of Loja, being obtained this way the possible consumers' information. Later on the market study was made that allowed to know that the demand develops it is of 78%, of the tourists that visit El Cisne, of the same one that the real demand is detailed that is 68% of the potential demand, with an effective demand of 78%, it was also determined the offerers of the product (key rings of resin), what facilitated to make the balance between the offer and the demand, as well as the unsatisfied demand that is of 423.229 key rings in the year of study. In the technical study, the installed capacity was determined of 49.275 key rings a year, with which will cover the 11, 41% of the unsatisfied demand; to the beginning of the production 75% of the installed capacity, the same one was used that 5% of the installed capacity, every two years will be ascended. In the administrative study, it was delineated the legal base and the managerial structure and the respective flowcharts and function manuals; as well as the number was determined of personal necessary for the setting in march of the project, of which one will be able to contribute with 5 direct positions in the labour market. Regarding the financial study the investment settled down of 21.947,62; of which 54,44% will be financed with own capital and 45,56% with a credit granted by BNF with an interest rate of 10,5%. The unitary cost of production is of 1,45 dollars, taking into account this value more the margin of utility one has the selling price to the public of 2,03 dollars that are in agreement to the competition. When carrying out the evaluation of the project it was determined that after having recovered the investment one will have a benefit of 66673,77 dollars with an Internal Rate of Return of 55,12% that is bigger to the discount rate; of each invested dollar one will have 18 cents of utility; the period of capital recovery is of 2 years, 3 months and 27 days; if the costs are increased until 6,36% or the revenues of the diminish 5,43% the project it is not sensitive; for what I can conclude that the project is feasible the indicators demonstrate financially since this way it